Produksi Baling-Baling Kapal dari Logam Daur Ulang melalui Teknik Pengecoran Logam - Akhyar Akhyar; Khairil Khairil; Ahmad Farhan; Masri Ibrahim; Suhaeri Suhaeri (Jurnal Teknik Mesin Unsyiah, 2020)
The boat propellers are needed for fishing boats in Aceh Province, considering that most Acehnese people geographically live along the coastline. Their income apart from farmers is fishermen. Currently, the metal ship propellers are imported from outside Aceh Province, so metal casting technology is needed to produce these ship propellers. There is already a small-scale industrial for metal casting, and the location is in Baet Lampuot - Aceh Besar District. The metal casting industry is currently producing rencong souvenirs to support tourism. However, when the Covid-19 Pandemic hit Aceh in particular and Indonesia in general, there are needed an alternative metal production business with other types of product variants, one of which was a ship cast-propeller. Based on this, Mechanical Engineering and FKIP Physics Department of Universitas Syiah Kuala improve the rencong metal casting industry to develop its products, to produce ship propellers through the Higher Education Leading Community Empowerment Program (PPMUPT) funded by the Ministry of Research and Technology /National Research and Innovation Agency of the Republic of Indonesia (RISTEK/ BRIN). The ship propeller product developed from waste metal, it recycled through metal casting technology. So the program and technology developed, is very useful not only for growing the regional economy but also in terms of handling the environment by recycling waste metal. Therefore, the community service program carried out by Mechanical Engineering and FKIP Physics Department of Universitas Syiah Kuala is right on target and in line with expectations.